Exploration of the Structure-Activity Relationship of 1,2,4-Oxadiazole Antibiotics - Ding, Derong (2015)
We have recently disclosed the discovery of the class of 1,2,4-oxadiazole antibiotics, which emerged from in silico docking and scoring efforts. This class of antibacterials exhibits Gram-positive activity, particularly against Staphylococcus aureus. We define the structure–activity relationship (SAR) of this class of antibiotics with the synthesis and evaluation of a series of 59 derivatives with variations in the C ring or C and D rings. A total of 17 compounds showed activity against S. aureus. Four derivatives were evaluated against a panel of 16 Gram-positive strains, inclusive of several methicillin-resistant S. aureus strains. These compounds are broadly active against Gram-positive bacteria.